2004
DOI: 10.1002/nbm.924
|View full text |Cite
|
Sign up to set email alerts
|

Iron oxide MR contrast agents for molecular and cellular imaging

Abstract: Molecular and cellular MR imaging is a rapidly growing field that aims to visualize targeted macromolecules or cells in living organisms. In order to provide a different signal intensity of the target, gadolinium-based MR contrast agents can be employed although they suffer from an inherent high threshold of detectability. Superparamagnetic iron oxide (SPIO) particles can be detected at micromolar concentrations of iron, and offer sufficient sensitivity for T 2 (*)-weighted imaging. Over the past two decades, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
1,135
0
12

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 1,408 publications
(1,159 citation statements)
references
References 123 publications
(145 reference statements)
12
1,135
0
12
Order By: Relevance
“…This brightness transition can significantly increase the detection sensitivity for theT 2 -type paramagnetic agents. This in vivo finding confirmed our previous in vitro studies on the MIONs [35], suggesting that T 1ρ -weighted imaging provides a promising method to overcome the "black holes" effect caused by the super-paramagnetic iron oxide (SPIO) in following the cellular or molecular events [36]. This result also highlights a possibility of acquiring angiography images without using paramagnetic agents.…”
Section: Rat Cerebral Vasculaturesupporting
confidence: 86%
“…This brightness transition can significantly increase the detection sensitivity for theT 2 -type paramagnetic agents. This in vivo finding confirmed our previous in vitro studies on the MIONs [35], suggesting that T 1ρ -weighted imaging provides a promising method to overcome the "black holes" effect caused by the super-paramagnetic iron oxide (SPIO) in following the cellular or molecular events [36]. This result also highlights a possibility of acquiring angiography images without using paramagnetic agents.…”
Section: Rat Cerebral Vasculaturesupporting
confidence: 86%
“…Another class of inorganic nanoparticles, superparamagnetic iron oxide (SPIO) nanoparticles, have shown great promise in magnetic resonance imaging (MRI) 7 , 8 . SPIO nanoparticles have a high transverse relaxivity, r 2 , which results in negative contrast on T 2 -weighted images.…”
Section: Introductionmentioning
confidence: 99%
“…The high susceptibility difference between CA and surrounding tissue can be exploited to generate a negative contrast, and several studies have indeed demonstrated that SPIO labeling allows the detection of grafted cells in vivo with high sensitivity. 21,22 A serious issue is the particulate nature of SPIOs, which make them a target for phagocytosis by activated reticulo-histiocytic cells. SPIOs have sizes ranging from 120 to 180 nm.…”
Section: Introductionmentioning
confidence: 99%